Strength Optimization Models for A Multi-Variant Binder Concrete using Osadebe’s Optimized Mixes - Akeke, G. A.; Ewa, D.E; Ibiang, D. O. (International Journal of Advanced Engineering Research and Science, 2022)
Cement production has now inevitably become associated with increased health risks and unpalatable economic implications. As a result, it has become imperative that concrete be produced from locally sourced, naturally occurring and eco-friendly materials that can either partially or fully replace cement in concrete, and yet maintain its structural viability and constructional adequacy. This paper therefore focused on assessing the structural and strength properties of a three-binder concrete with Rice Husk Ash (RHA) and Mound Soil (MS) as partial replacements of Ordinary Portland Cement (OPC). Compressive strength tests were conducted on the concrete cubes after 28 days of curing. The laboratory work was done with the guidance of the provisions of the Osadebe’s model for the actual components of the MS-RHA concrete. There were ten (10) test points and ten (10) control points taken for this research. The highest compressive strength predicted in this work was 35.0N/mm2 corresponding to a Water/Cement ratio of 0.55 with mix ratio of 0.55:1:1:2 for a 10% replacement of OPC with 5% each of RHA and MS. The least value predicted by the model was 15.20N/mm2 with W/C ratio of 0.47 in mix ratio 0.47:1:5:8. The adequacy of the model was tested using the student’s t-test and passed for adequacy, with tcalculated = 0.303, less than ttable = 2.262, thereby annulling the alternate hypothesis and sustaining the null hypotheses respectively proposing significant and insignificant differences between the experimental and predicted values.